2005
DOI: 10.1103/physrevb.72.035212
|View full text |Cite
|
Sign up to set email alerts
|

Jahn-Teller distortion and ferromagnetism in the dilute magnetic semiconductors GaAs:Mn and cubic GaN:Mn

Abstract: Using first-principles total-energy methods, we investigate Jahn-Teller distortions in III-V dilute magnetic semiconductors, GaAs:Mn and GaN:Mn in the cubic zinc blende structure. The results for an isolated Mn impurity on a Ga site show that there is no appreciable effect in GaAs, whereas, in GaN there is a Jahn-Teller effect in which the symmetry around the impurity changes from T d to D 2d or to C2v. The large effect in GaN occurs because of the localized d 4 character, which is further enhanced by the dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 66 publications
4
29
0
Order By: Relevance
“…One thus expects a strong local Jahn-Teller instability toward splitting the degeneracy into 2 + 1. Indeed, the Jahn-Teller instability has been found in previous studies [55,56]. It is easier to describe this local physics using an "effective" d 4 picture.…”
mentioning
confidence: 99%
“…One thus expects a strong local Jahn-Teller instability toward splitting the degeneracy into 2 + 1. Indeed, the Jahn-Teller instability has been found in previous studies [55,56]. It is easier to describe this local physics using an "effective" d 4 picture.…”
mentioning
confidence: 99%
“…We obtained a value of 1.9 eV comparing notably better with experiment (1.8±0.2 eV [37]) than PBE calculations (1.6 eV). In order to test the predictive capability of the procedure, we have repeated the calculations for Mn Ga in GaAs, for which Mn is experimentally found in a d 5 configuration [36]. In this case, the splitting of the t 2 states drops to ∼ 0.2 eV, and no Jahn-Teller effect is theoretically found using HSE or experimentally expected [36].…”
mentioning
confidence: 99%
“…In order to test the predictive capability of the procedure, we have repeated the calculations for Mn Ga in GaAs, for which Mn is experimentally found in a d 5 configuration [36]. In this case, the splitting of the t 2 states drops to ∼ 0.2 eV, and no Jahn-Teller effect is theoretically found using HSE or experimentally expected [36]. Furthermore, the HSE band structure for Mn in GaAs (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interests are further caused by the prediction of ferromagnetism at room temperature and even above in these materials [2][3][4]. Of the established DMSs, Mndoped GaN films are predicted to have the higher Curie temperatures (T C ) above room temperature [5] and many efforts involving the controlled fabrication of these materials as well as to explore the characterization and their physical properties have been developed [6][7][8]. It has been suggested that the ferromagnetism (FM) in (Ga,Mn)N could arise from the formation of magnetic clusters [9].…”
Section: Introductionmentioning
confidence: 99%